2020
DOI: 10.1016/j.jcyt.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Release kinetic of pro- and anti-inflammatory biomolecules from platelet-rich plasma and functional study on osteoarthritis synovial fibroblasts

Abstract: Background aims: This study evaluated the release kinetics of numerous representative and less studied plateletrich plasma (PRP) cytokines/chemokines with regard to the effects of various cellular compositions and incubation times. In addition, the biological effects of different PRPs on osteoarthritis synovial fibroblasts in vitro were tested. Methods: Peripheral whole blood was collected from healthy donors, and pure platelet-rich plasma (P-PRP), leukocyte-rich platelet-rich plasma (L-PRP) and platelet-poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Indeed, several studies showed an anabolic effect of PRP on cartilage tissue [ 16 , 30 ] and chondrocyte metabolism [ 30 , 57 , 71 ]. The role of PRP on synoviocyte metabolism appeared more complex with both pro- and anti-inflammatory effects depending in part of PRP characteristics [ 4 , 7 , 64 , 92 ] although in vivo studies brought out rather an anti-inflammatory effect of PRP on synovial tissue [ 16 , 50 ]. Some preliminary studies in humans also seem to show beneficial homeostatic effects of PRP injections on joint tissues [ 3 , 29 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several studies showed an anabolic effect of PRP on cartilage tissue [ 16 , 30 ] and chondrocyte metabolism [ 30 , 57 , 71 ]. The role of PRP on synoviocyte metabolism appeared more complex with both pro- and anti-inflammatory effects depending in part of PRP characteristics [ 4 , 7 , 64 , 92 ] although in vivo studies brought out rather an anti-inflammatory effect of PRP on synovial tissue [ 16 , 50 ]. Some preliminary studies in humans also seem to show beneficial homeostatic effects of PRP injections on joint tissues [ 3 , 29 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…that may contribute to the therapeutic effects. Preclinical studies have shown that the granule secretions have mainly a homeostatic effect with anabolic and anti-inflammatory impacts on joint tissues and cells [ 16 , 30 , 50 , 57 , 64 , 71 , 92 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is an increasing awareness on the complexity of PRP itself in light of its heterogeneity according to the preparation and application modalities, and the most suitable protocol to exploit PRP potential by concentrating the most effective cluster of growth factors to help meniscal healing remains to be defined. 8,39 Thus, the oversimplified nature of the current meta-analysis has to be recognized, and future studies need to better investigate what kind of augmentation could provide the best results and how to deliver it to the lesions. This will eventually lead to obtaining a standardization of meniscal repair augmentation procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Beside showing an overall safety of intra-articular injections, the meta-analysis could not investigate its superiority versus placebo, and results were limited to an indirect comparison between PRP and HA which was not able to detect differences. Moreover, the complexity of the PRP field would require more studies to investigate many different features, which could affect the final outcome, such as the concentration of platelets, the presence of leukocytes, as well as the possibility of cryopreserving PRP or using it fresh, the choice of activation method, and so on [69][70][71][72][73]. Thus, further high-quality studies are needed to support the benefit of PRP in ankle OA patients, to clearly understand potential and indication compared with the other available injective options.…”
Section: Discussionmentioning
confidence: 99%